Use of adherence monitoring in drug contracts tied to outcomes: put patients first. (7th March 2022) - Bartholomew, Theodore; Naci, Huseyin; Robertson, Emma; Schmidt, Harald
Abstract : Theodore Bartholomew and colleagues examine how contracts linking drug payments to effectiveness may affect patient trust and autonomy